2014
DOI: 10.1103/physrevb.90.064410
|View full text |Cite
|
Sign up to set email alerts
|

Breathing modes of confined skyrmions in ultrathin magnetic dots

Abstract: The dynamics of individual magnetic skyrmions confined in ultrathin film dots is studied theoretically. The systems considered are transition metal ferromagnets possessing perpendicular magnetic anisotropy and particular attention is given to the dynamic response of the skyrmions to perpendicular driving fields. By using micromagnetics simulations, it is shown that breathing modes can hybridize with geometrically-quantized spin wave eigenmodes of the circular dots considered, leading to distinct features in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 48 publications
9
136
1
Order By: Relevance
“…Dynamics of skyrmions in isolated disk was already investigated and our simulations are in agreement with these results. 11 The ground state of the isolated disk is presented in Fig. 1(a).…”
Section: 2mentioning
confidence: 99%
“…Dynamics of skyrmions in isolated disk was already investigated and our simulations are in agreement with these results. 11 The ground state of the isolated disk is presented in Fig. 1(a).…”
Section: 2mentioning
confidence: 99%
“…Additional reason for that are perspective applications of the RT isolated skyrmions in nanoscale devices 33 . Isolated skyrmions, conditions required for their existence in patterned films [11][12][13][14]23,34,35 , and the dynamics of isolated skyrmions in magnetic films and nanodots have been simulated 29,33,36,37 and experimentally explored 38 . Lin et al 29 simulated dynamics of isolated skyrmion in an infinite film and found one gyrotropic mode, several breathing and non-symmetric skyrmion shape modes in the area of the skyrmion stability.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of the skyrmion breathing modes in cylindrical dots were presented in Ref. 36 . Spin excitation spectrum in presence of the magnetic vortex (half-skyrmion) ground state was investigated in detail in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest frequency mode (purple dot and black dashed line) corresponds to the so called breathing skyrmion modes. 19 The higher frequency mode (marked by black dot) is a high order quantized mode of the same type of the radially symmetric excitations. Continuous transition of the mode along the path allows to find corresponding modes in the vortex state, in the Bloch-like and Néel-like skyrmions.…”
Section: Fig 3 (Color Online)mentioning
confidence: 99%
“…Non zero-frequency modes are expected for the solitons in magnetic dots because the soliton energy depends on the soliton position and soliton radius due to existence of the sample edges. Even though several papers have been already published on the skyrmion dynamical excitations in restricted geometry, [19][20][21][22][23] the consensus regarding the classification of the spin eigenmodes over skyrmion background in nanodots has not been reached so far. Also a transition between the dynamical vortex and skyrmion modes has not been explored.…”
mentioning
confidence: 99%